PERBEDAAN STRUKTUR KOMUNITAS NEMATODA TANAH ANTARA LAHAN GAMBUT ALAMI DAN BEKAS TERBAKAR DI KECAMATAN GAMBUT KALIMANTAN SELATAN - Abdul Gafur (Universitas Lambung Mangkurat, 2008)
Nematode community structures of peaty soils have been studied for the use of soil nematodesas biological indicator of soil ecological condition and biodiversity. Taxon diversity, trophicgroup composition, life strategy groups, and guilds of nematodes were compared betweennatural and fire-disturbed locations in a peatland in Gambut Subdistrict, South Kalimantan.Comparison was also made between the first and the second 10 cm of soils. The resultsindicated that natural and fire-disturbed peaty soils did not differ significantly in total and pertaxon nematode densities and diversity index. However, a predictor species richness suggestedthat natural sites have higher species richness. The two site conditions did not differ incompositions of trophic and life strategy groups, leading to a similarity in their maturityindexes. However, the two site conditions showed differences in nematode guild proportions. Innatural condition the first and second 10 cm of soil did not differ in nematode composition,while in fire-disturbed sites the upper part of the soil hosted a higher density of nematodes. Thepresent study implies that optimizations in soil sampling and nematode extraction are requiredbefore the use of soil nematodes as biological indicator of soil condition can be achieved in anyparticular area.